Development Strategy System Information Management in Support Organizational Digital Transformation - Hendra Jatnika; Mia Kusmiati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Goals – Goals from studies This is For explore approach strategic in development System Information Management (SIM) as integral part in support digital transformation of modern organizations. Study This emphasize importance integration technology information , effective data management as well as improvement digital competence resources Power man in operation system. Design/ methodology / approach – Conceptual article This use method review library with analyze various work relevant academic and technical manuals , in particular related implementation of SIM in the sector public and private . Study This referring to the works Jatnika et al. (2022–2024), including utilization Microsoft Office applications as skills supporting basis​ organizational digital literacy . Findings – Findings studies This show that SIM development is not just effort technical , but rather need strategic in support digital transformation . Key strategies covers design modular systems , data mining integration , training programs based users , and evaluation system in a way periodic . Components This allows organization build responsive and adaptive SIM ecosystem . Implications practical – Organizations that want to do digital transformation is necessary invest in development digital capabilities of sources Power the human as well as ensure effectiveness use developed SIM system in a way strategic can become driving force main in increase efficiency , accuracy , and capability taking decision across work units . Originality / value – Study This offers a conceptual model structured about development of SIM in context digital transformation , based on literature applications and needs organizations in the real world . This article give outlook practical for taker policy , IT managers , and HR developers .